A conditional case for the moral justifiability of germline editing for the prevention of HIV - Lehong, Mokgadi Elizabeth (My University, 2021)
In “A Conditional Case for the Moral Justifiability of Germline Editing for the Prevention of HIV”, the morality of human germline editing is divided into issues relating to safety and efficacy and those raised by the potential success of the procedure. Significant to this moral discussion is the experiment that led to the first gene-edited babies, the ‘CRISPR experiment’. Using this experiment as the foundation of my discussion I attempt to answer the question, “Is it morally justifiable to use germline editing to prevent HIV transmission?”. The main defence of the thesis is that using germline editing to prevent HIV transmission would be morally justified provided that (a) the current scientific risks and safety concerns associated with its use were resolved, and (b) an effective method of using germline editing for this purpose were proven. Under this argument, reproductive rights and duties associated with the human germline are explored to argue for the existence of transgenerational relationships that binds parents to exercise care and responsibility towards their future children. Furthermore, arguments for germline editing are presented in terms of the principle of procreative beneficence to advocate for promoting the wellbeing interests of prospective generations in reproductive choices. Countering critics relating to the claims that germline editing violates human dignity, the natural identity of persons, consent and other possible societal concerns (eugenics, discrimination and social justice); I invoke the defence that humans are morally obliged to promote and safeguard the well-being interest of their future generations by pursuing the potential significance of the procedure in advancing human lives through treatment and prevention of diseases. Following the discussion on possible uses of germline editing, including a comparison with the existing methods of artificial reproduction based on their shortfalls, benefits and purpose in reproductive medicine; I argue for the moral use of germline editing for therapeutic purposes only and further make recommendations based on the proper regulation of the procedure to promote social justice and solidarity.
A research report submitted in fulfilment of the requirements for the degree Masters of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021